Analysis of glycosylated cardiolipins from thermophilic bacteria using GC-MS and LC-ESI-MS/MS methods - Kyselová, Lucie; Řezanka, Tomáš (Journal of pharmaceutical and biomedical analysis, 2024)
Unusual glucose-substituted cardiolipins (Glcx-CLs) in three genera of thermophilic bacteria, having more than one glycosidically linked glucose to the hydroxyl of the central glycerol of Glcx-CLs were identified for the first time in thermophilic bacteria of the genera Geobacillus, Meiothermus, and Thermus. The number of glucoses reached up to five units. The structure of glycosidically linked oligosaccharides was determined based on shotgun analysis MS (electrospray high-resolution tandem mass spectrometry), partially methylated alditol acetates were identified by GC-MS, both electron ionization (EI) and positive chemical ionization (PCI), hydrophilic interaction liquid chromatography (HILIC) separation and identification of CLs glycosides by high resolution MS-ESI, and digestion by specific glycosidases.
Keywords: kardiolipiny; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, Liquid; Spectrometry, Mass, Electrospray Ionization; Bacteria; Cardiolipins; plynová chromatografie s hmotnostně spektrometrickou detekcí; tandemová hmotnostní spektrometrie; glukosa; chromatografie kapalinová; Gas Chromatography-Mass Spectrometry; Tandem Mass Spectrometry; Glucose